A Review Of IL-17 Relation With Microbiome In Metabolic Disorder - Najmi, Nuroh; Kuswandani , Faisal; Rafisa, Anggun; Falisha Febriane Balafif (Sean Institute, 2024)
The relationship between IL-17 and the microbiome remains an area requiring extensive research. IL-17, a pro-inflammatory cytokine, plays a crucial role in immune function, particularly in its interactions with the microbiome, especially within the intestinal digestive system. In metabolic diseases linked to inflammation, this connection underscores the importance of understanding cytokine activity and the microbiome's response within the body. In this literature review, three articles were retrieved from a single database, exploring the relationship between IL-17, metabolic diseases, and the microbiome.